HUBUNGAN PARITAS DAN USIA IBU DENGAN KEJADIAN HIPEREMESIS GRAVIDARUM TINGKAT II DAN III DI RUMAH SAKIT BHAYANGKARA MAKASSAR - Nurhikmah Nurhikmah (Stikes Graha Edukasi Makassar, 2020)
The purpose of this research is to know the relation of parity and maternal age with the incidence of level II and III hypermesis gravidarum at Bhayangkara Makassar Hospital 2014. Method: This study used Cross Sectional Study approach, 144 people population and 59 samples, secondary data using record medical, data processing with computerized program and data analysis with Chi-Square. Results: The results of the parity distribution obtained from 59 total samples were 35 people (59.4%) with high risk parity, while 24 people (40.7%) with low risk parity means there was a parity relationship with the incidence of hyperemesis gravidarum at the Hospital Bhayangkara Makassar, while the distribution of mother age of research shows that from 59 total samples there are 13 people (22,0%) with high risk mother age and 46 people (78,0%) with low risk mother age at Bhayangkara Makassar Hospital 2014. Discussion : High risk parity in order to use one of the contraceptive methods to exclude or delay pregnancy so that hyperemesis gravidarum can be minimized. Continuing pregnancy checking regardless of low-risk age and high-risk age because all pregnancies are at risk. Conclusion: The conclusion of this research is that there is a parity relationship with the incidence of hyperemesis gravidarum level II and III in Bhayangkara Makassar Hospital 2014 and there is no relation between maternal age and hyperemesis gravidarum level II and III at Bhayangkara Makassar Hospital